Migrant smuggling in Canada: possible lessons for beyond borders - Winterdyk, John A. (NBP. Nauka, bezbednost, policija, 2018)
Even though migration has been seen as an expression of people’s willingness to overcome adversity to find and live a better life, within the complex socio-political and diverse world of today, it has become a problematic phenomenon in Canada, and elsewhere. Aside from definitional challenges, the illegal movement of people presents a wide range concerns for States (e.g., accommodating the numbers, migrant integration, socio-cultural barriers, etc.). Defining and responding to ‘irregular migration’ is fraught with a number of challenges but recent cases in Canada provide possible options to ensure the safety and security of illegal migration movements not only in Canada but potentially internationally. An intervention and prevention model based on engagement, empathy, and empowerment (i.e. 3E’s) is discussed.